Cross-Talk between Diet-Associated Dysbiosis and Hand Osteoarthritis - Silvestre, Marta P (2020)
Funding: This research was funded by the National Funds through FCT—Fundação para a Ciência e a Tecnologia within CINTESIS, R&D Unit reference UID/IC/4255/2013 and within CHRC R&D Unit reference UIDB/04923/2020